Evaluation of the Difference in the Content of Essential and Non-Essential Elements in Wild Boar and Swine Tissues Sampled in the Same Area of Northern Italy - Draghi, Susanna; Spinelli, Michele; Fontanarosa, Carolina; Curone, Giulio; Amoresano, Angela; Pignoli, Elisabetta; Cagnardi, Petra; Vigo, Daniele; Arioli, Francesco; Materazzi, Stefano; Risoluti, Roberta; Di Cesare, Federica (Animals (Basel), 2024)
This study aimed to investigate the exposure of wild boars and swine from semi-extensive farms in the same area to essential and non-essential elements, measuring their concentration in liver and muscle. Furthermore, the study explored the influence of factors such as sex, age, and the sampling location on wild boars. Higher liver element concentrations were observed in both wild boars and swine. Geographical comparisons revealed minor differences. Young wild boars showed significantly higher Cu, Se, Cd, and Cr levels, while older subjects exhibited elevated Mn levels, reflecting age-related element absorption variations. No significant sex-based variations were noted. Comparing wild boars to swine, wild boars had more non-essential elements due to their foraging behavior and a larger home range. Conversely, swine exhibited a greater prevalence of essential elements, potentially resulting from dietary supplementation.